Size and Shape Directed Novel Green Synthesis of Plasmonic Nanoparticles Using Bacterial Metabolites and Their Anticancer Effects - Patil, Snehal; Sastry, Murali; Bharde, Atul (Frontiers in Microbiology, 2022)
The growing need for developing new synthesis methods of plasmonic nanoparticles (PNPs) stems from their various applications in nanotechnology. As a result, a variety of protocols have been developed for the synthesis of PNPs of different shapes, sizes, and compositions. Though widely practiced, the chemical synthesis of PNPs demands stringent control over the experimental conditions, often employs environmentally hazardous chemicals for surface stabilization, and is frequently energy-intensive. Additionally, chemically obtained PNPs require subsequent surface engineering steps for various optoelectronic and biomedicine applications to minimize the toxic effects and render them useful for targeted drug delivery, sensing and imaging. Considering the pressing need to develop environmentally-friendly technology solutions, ‘greener’ methods of nanoparticle synthesis are gaining importance. Here we report on the biological synthesis of plasmonic nanoparticles using bacterial metabolites. A peptide-based siderophore pyoverdine and a blue-green pigment pyocyanin obtained from a marine strain of Pseudomonas aeruginosa rapidly produced plasmonic nanoparticles of gold and silver in an aqueous environment. The morphology of plasmonic nanoparticles could be modulated by tuning the concentration of these metabolites and the reaction time. Exposure of pyoverdine to chloroauric acid resulted in anisotropic gold nanoparticles. On the other hand, pyocyanin produced a highly monodispersed population of gold nanoparticles and anisotropic silver nanoparticles. Biologically obtained gold and silver nanoparticles retained pyoverdine and pyocyanin on the nanoparticle surface and were stable for an extended period of time. The biologically obtained gold and silver plasmonic nanoparticles displayed potent anticancer activities against metastatic lung cancer cells. Biogenic nanoparticles were rapidly internalized by cancer cells in high quantity to affect the cellular organization, and karyoplasmic ratio, indicating the potential of these nanoparticles for cancer nanomedicine.